One-pot synthesis of PdAu bimetallic composite nanoparticles and their catalytic activities for hydrogen peroxide generation - Xiao, Xiangyun; Kang, Tae-Uook; Nam, Hyobin; Bhang, Suk Ho; Lee, Seung Yong; Ahn, Jae-Pyung; Yu, Taekyung (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2018)
We report a facile one-pot aqueous-phase synthesis of PdAu bimetallic nanoparticles with different Pd/Au ratio. The synthesis was conducted by co-reduction of Pd and Au precursor using ascorbic acid as a reducing agent and in the presence of polyallylamine hydrochloride (PAH). By high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and energy-dispersive X-ray spectrometry (EDS) analyses, we found that the synthesized nanoparticles had an onion-like core/shell/shell/shell structure with Au-rich core, Pd-rich shell, Au-rich shell, and Pd shell, respectively. We also investigated the catalytic performance of the synthesized PdAu nanoparticles toward hydrogen peroxide generation reaction.
Keywords: FACILE SYNTHESIS; SHELL; OXIDATION; ALLOY; DEPOSITION